Genome-Wide Detection of Structural Variations Reveals New Regions Associated with Domestication in Small Ruminants. (15th July 2021) - Cumer, Tristan; Boyer, Frédéric; Pompanon, François
Abstract: During domestication processes, changes in selective pressures induce multiple phenotypical, physiological, and behavioral changes in target species. The rise of next-generation sequencing has provided a chance to study the genetics bases of these changes, most of the time based on single nucleotide polymorphisms (SNPs). However, several studies have highlighted the impact of structural variations (SVs) on individual fitness, particularly in domestic species. We aimed at unraveling the role of SVs during the domestication and later improvement of small ruminants by analyzing whole-genome sequences of 40 domestic sheep and 11 of their close wild relatives ( Ovis orientalis ), and 40 goats and 18 of their close wild relatives ( Capra aegagrus ). Using a combination of detection tools, we called 45, 796 SVs in Ovis and 15, 047 SVs in Capra genomes, including insertions, deletions, inversions, copy number variations, and chromosomal translocations. Most of these SVs were previously unreported in small ruminants. 69 and 45 SVs in sheep and goats, respectively, were in genomic regions with neighboring SNPs highly differentiated between wilds and domestics (i.e., putatively related to domestication). Among them, 25 and 20 SVs were close to or overlapping with genes related to physiological and morpho-anatomical traits linked with productivity (e.g., size, meat or milk quality, wool color), reproduction, or immunity. Finally, several of the SVs differentiated between wilds and domestics would not have been detected by screening only the differentiation of SNPs surrounding them, highlighting the complementarity of SVs and SNPs based approaches to detect signatures of selection.